“AMIR TEMUR AS A STATE BUILDER AND MILITARY LEADER” - Teshaboyeva Nafisa Zubaydulla qizi; Qaxramonova Nuridiyda Jaxongir qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract Amir Temur, often remembered as Tamerlane, remains a figure of profound historical complexity, simultaneously lauded as a brilliant military strategist and state builder, and condemned as a ruthless conqueror. This article critically examines Temur’s multifaceted legacy, analyzing his contributions to statecraft, military innovation, and cultural patronage against the backdrop of the extensive human cost of his campaigns. It investigates the scholarly debates surrounding the authenticity and interpretive value of primary sources, particularly the contested Tuzukat-i Timuri, and explores how these discussions shape contemporary understandings of Temur’s governance principles. By synthesizing existing academic perspectives and addressing the inherent dualities of his rule, this analysis seeks to reconcile the images of Temur as both a constructive force for state consolidation and a destructive agent of widespread devastation. The article aims to offer a nuanced understanding of his enduring influence, particularly in modern national narratives.